Analysis of catalytic control of tar quality during coal pyrolysis and the coke behavior on catalyst surface - Weiren BAO; Qian WANG; Ting LI; Qian TIAN; Nichen WANG; Lunjing YAN; Meijun WANG; Liping CHANG (Meitan xuebao, 2024)
The low-rank coal pyrolysis technology with tar upgrading by catalyst is a clean and efficient coal conversion technology that ensures national energy security while also meeting the “carbon peaking and carbon neutrality” goals. The catalytic effects of metals, metal oxides, natural minerals, zeolites, and carbon-based catalysts on coal and pyrolysis volatiles are discussed due to the complexity in controlling tar quality and coke behavior. It also evaluates the effects of each type of catalysts on the distribution and composition of pyrolysis products, comparing their advantages and disadvantages. The differences in the physical and chemical properties of various catalysts, as well as their relationship with catalytic performance, are explored in detail, and the action mechanism of various catalysts is revealed by combining the bond breaking behavior of C—C, C—H, C=C, —OH, C=O, C—O and —COOH in coal and pyrolysis volatiles. Based on the studies above, aiming at the problems with low-tar yield and poor-tar quality during the catalytic process, it is proposed to use internal small molecule hydrogen donors and external solid/gaseous hydrogen donors activated by metal, particularly the transition metal modified catalysts, for in-situ hydrogen supply to heavy components cracking fragments in order to increase tar yield and improve tar quality during the catalytic process. Furthermore, to solve the problem of catalyst deactivation caused by coke, the chemical and physical characteristics and composition of coke, as well as the causes of coke formation, are examined in depth. Several effective strategies to coke inhibition are proposed, commencing with the design of the catalysts and the pyrolysis reaction system. Combining metal active sites with multi-level pores, bimetallic modification to control the ratio of Lewis and Brønsted acid sites, the synthesis of dual-functional catalysts with basic and acidic properties, and the introduction of hydrogen-rich small molecules such as H2O, CH4, C2H6, and CH3OH to control volatiles composition all contribute to effective coke suppression methods. The study can serve as a theoretical basis for the advancement of catalytic pyrolysis technology for low rank coal.